Direct synthesis of Fe-ZSM-5 zeolite and its prospects as efficient electrode material in methanol fuel cell. (December 2015) - Mohan, N.; Cindrella, L.
Abstract: New method of direct synthesis of Fe-ZSM-5 zeolite using tetrapropyl ammonium bromide (TPABr) as the template is reported in this study. The synthesis was based on one step procedure and did not involve the usual ion-exchange step to effect incorporation of the metal ion. The zeolite sample was characterized by XRD, FT-IR, TGA, SEM with EDX, and BET adsorption techniques. The average diameter of the porous particle of zeolite was about 10 µm and it was a spherical cluster of crystals of about 141 nm long along one of its axis. Zeolite-modified glassy carbon electrode (GCE) was prepared by using the mixture of the synthesized zeolite and carbon black (Vulcan X-72) and casting it as a thin layer. With modified GCE as the working electrode, the oxidation of methanol in alkaline medium was studied by cyclic voltammetry. The response of the electrode for methanol oxidation in alkaline medium is promising and it highlights the candidature of the synthesized material for methanol fuel cell. The electrochemical behavior of Fe-ZSM-5 in acidic medium reveals the oxidation state of iron in the zeolite. Cationic iron in the zeolite framework imparts electrocatalytic activity for methanol oxidation.